Pengaruh Cita Rasa, Pengalaman Pelanggan, Digital Marketing terhadap Minat Beli Ulang Pelanggan - Narita Gayatri; Aprilia Dian Evasari; Endah Kurniawati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of taste, customer experience, and digital marketing on repurchase intention at Mie Ayam Panggang Demi Apa in Kediri. In the increasingly competitive culinary industry, business owners are required to maintain taste consistency, create memorable customer experiences, and optimally utilize digital platforms in their marketing strategies. These three factors are believed to play an essential role in shaping consumer behavior, particularly in encouraging repeat purchases. The research applied a quantitative survey method involving 90 respondents selected using Slovin’s formula. Respondents were customers who had made at least two purchases within the last month. Data analysis was conducted using SPSS version 26 with several statistical tests, including validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The findings indicate that taste, customer experience, and digital marketing each have a positive and significant influence on repurchase intention, both partially and simultaneously. The R² value of 0.447 shows that 44.7% of the variation in repurchase intention is explained by these three variables. Therefore, it is recommended that business owners consistently maintain product quality, enhance customer experience, and optimize digital marketing to build customer loyalty and ensure long-term business sustainability.